Nellie vs. Elizabeth : two daredevil journalists' breakneck race around the world - Hannigan, Kate (Calkins Creek, an imprint of Astra Books for Young Readers, 2022)
"Join two daredevil journalists, Nellie Bly and Elizabeth Bisland, as they race against each other--and the ticking clock--to circle the globe in fewer than 80 days. And by any means possible--ship, train, even foot! Bly, energetic and scrappy, and Bisland, poetic and sophisticated, shared one common goal: to prove that women could not only travel the world but were just as curious, capable, and courageous as any man. Did it really matter who won the race?"--Jacket flap.